Comparison of Intra Articular Platelet Rich Plasma with Corticosteroids in Patients with Temporomandibular Dysfunction - Sahar Usman; Sufyan Ahmed; Sana Iqbal; Mehwash Kashif; Mirza Hamid Baig; Ajeet Kumar; Uzma Shamsi (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
Objective: To evaluate comparison of intra-articular injection of Platelet Rich Plasma (PRP) and corticosteroids in patients with Temporo Mandibular Joint Dysfunction syndrome. Methods: This case-control study was conducted at Department of Oral Maxillofacial Surgery in a tertiary care hospital, Karachi. The inclusion criteria was patients with either gender aged from 25-50 years, previously diagnosed with TMJ dysfunctions syndrome not responding to conservative management. Patients with stage 3 & 4 TMD disease and uncontrolled comorbidities were excluded. After takinginformed consent predesigned questionnaire was used to collect information from patients, about their socio demographic and lifestyle-related factors. Based on clinical and radiological data as well as the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD), a diagnosis of TMPDS was established. PRP was injected into the upper joint space in the PRP group and triamcinolone in other group. Follow-up was conducted after one-week, one and third-month interval. Respectively evaluation of reduction in symptoms was conducted using VAS pain scoring system and other parameters were measured in millimeters by an unassisted maximum incisal opening method using Vernier Caliper. Data was analysed using SPSS v. 21. P-value > 0.05 was considered significant. Results: Total 16 (66.7 %) were females. Maximum age group which receives treatment was 38 years i.e. 4 (16.7%). Mean age was 32.75 + 5.01 years. It was evident that mouth opening increased significantly along with an increase in lateral protrusive movement from 6mm to 7 mm. Joint tenderness was reduced up to 50%. Although joint clicks slightly increased from 58.3% to 62.5%. When comparing the PRP group to control group, pain score was significantly reduced (p-value: <0.001). Conclusion: In patients with Temporo Mandibular Joint Dysfunction syndrome, it was discovered that intra-articular PRP injection was more successful in symptom reduction than corticosteroid injection